Delayed surgery versus nonoperative treatment for hip fractures in post-COVID-19 arena: a retrospective study of 145 patients. (7th September 2020) - Mi, Bobin; Chen, Lang; Tong, Dake; Panayi, Adriana C; Ji, Fang; Guo, Junfei; Ou, Zhiyong; Zhang, Yingze; Xiong, Yuan; Liu, Guohui
Abstract : Background and purpose — Following the outbreak of COVID-19 in December 2019, in China, many hip fracture patients were unable to gain timely admission and surgery. We assessed whether delayed surgery improves hip joint function and reduces major complications better than nonoperative therapy. Patients and methods — In this retrospective observational study, we collected data from 24 different hospitals from January 1, 2020, to July 20, 2020. 145 patients with hip fractures aged 65 years or older were eligible. Clinical data was extracted from electronic medical records. The primary outcomes were visual analogue scale (VAS) score and Harris Hip Score. Major complications, including deep venous thrombosis (DVT) and pneumonia within 1 month and 3 months, were collected for further analysis. Results — Of the 145 hip fracture patients 108 (median age 72; 70 females) received delayed surgery and 37 (median age 74; 20 females) received nonoperative therapy. The median time from hip fracture injury to surgery was 33 days (IQR 24–48) in the delayed surgery group. Hypertension, in about half of the patients in both groups, and cerebral infarction, in around a quarter of patients in both groups, were the most common comorbidities. Both VAS score and Harris Hip Score were superior in the delayed surgery group. At the 3-month follow-up, the median VAS score was 1 in the delayed surgery group and 2.5 in the nonoperative group (p < 0.001). Also, the percentage of complications was higher in the nonoperative group (p = 0.004 for DVT, p < 0.001 for pulmonary infection). Interpretation — In hip fracture patients, delayed surgery compared with nonoperative therapy significantly improved hip function and reduced various major complications.